Delineation of Potential Sites for Rice Cultivation Through Multi-Criteria Evaluation (MCE) Using Remote Sensing and GIS - Raza S.M.H. (2018)
© 2017, The Author(s).Punjab, Pakistan is famous for rice production in all over the world, but economic indicators are low toward rice contribution in the regional economy. Climatic and physical factors are responsible for rice yield degradation. Suitable land for rice cultivation can be mapped keeping in view these climatic and physical factors. In this research, rice cultivation season was calculated using Moderate Resolution Imaging Spectro-radiometer (MODIS) time series datasets for the complete year 2014. Landsat 8 thermal datasets were obtained for the rice cultivation season and temperature based growth variability maps were generated. The total area under investigation was 13,657 km2 out of which 931.61 km2 (6.8%) was found to be least suitable, 3316.69 km2 (24.2%) was moderately suitable, 6019.63 km2 (44%) was highly suitable and 3395.28 km2 (24.85%) was not suitable for rice crop cultivation. Results showed that highly suitable area was characterized by a temperature range between 21 and 32 °C, soil pH level between 5.5 and 7.2, soil type was < 78% clay and the soil was imperfectly drained. We compared land suitability map covering the complete land use with rice cultivated area only and found the results as follows: 592 km2 (5.9%) rice cultivation was in least suitable, 4385 km2 (44%) cultivation was in highly suitable, 2210 km2 (23.2%) cultivation was in moderately suitable and 1674 km2 (16.8%) cultivation was in not suitable regions. The techniques applied in this research may be used by local farmers to select cropping patterns and land suitability for rice crop.